2009
DOI: 10.1097/nmd.0b013e3181bea56e
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Self-Reported Attachment Styles, Interpersonal Dysfunction, and Borderline Personality Disorder

Abstract: Clinical theories of borderline personality disorder (BPD) identify attachment insecurity as the basis of its characteristic disturbed interpersonal functioning. The purpose of this study was to compare attachment ratings in rigorously diagnosed BPD, depressed (MDD), and nonborderline comparison groups and their correlations to features of interpersonal disturbance. Subjects self-reported ratings on attachment styles using the relationship questionnaire. BPD subjects reported higher scores on both preoccupied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(51 citation statements)
references
References 27 publications
6
45
0
Order By: Relevance
“…Indeed, as reported by previous studies based on the RQ (Brennan & Shaver, 1998;Choi-Kain, Fitzmaurice, Zanarini, Laverdiere, & Gunderson, 2009;Dutton, Saunders, & Starzomski, 1994;Hoermann, Clarkin, Hull, & Fertuck, 2004), our data supports 14 the fact that a fearful attachment pattern is also relevant to BPD. Preoccupied and fearful patterns both imply negative working models of self, namely a representation of oneself as being unworthy and unacceptable that goes along with excessive anxiety and dependency in close relationships.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, as reported by previous studies based on the RQ (Brennan & Shaver, 1998;Choi-Kain, Fitzmaurice, Zanarini, Laverdiere, & Gunderson, 2009;Dutton, Saunders, & Starzomski, 1994;Hoermann, Clarkin, Hull, & Fertuck, 2004), our data supports 14 the fact that a fearful attachment pattern is also relevant to BPD. Preoccupied and fearful patterns both imply negative working models of self, namely a representation of oneself as being unworthy and unacceptable that goes along with excessive anxiety and dependency in close relationships.…”
Section: Discussionsupporting
confidence: 79%
“…the fact that the same risk and protective factors could result in multiple outcomes (Hosman, 2011), in this paper a special emphasis was put on the role of the attachment between caregiver and a child. This is supported by different studies that have shown that borderline personality disorder and substance use disorders can be seen as attachment problems (Kassel, Wardle & Roberts, 2007;Choi-Kain et al, 2009;Thornberg & Lyvers, 2010). Furthermore, depending on the context, attachment could enhance the risks, as well as strengthen protection, and therefore is understood as an important concept that should be taken into account in prevention interventions.…”
Section: Resultssupporting
confidence: 57%
“…Finally, inconsistent support from caretakers during childhood is most often associated with preoccupied attachment which is thought to produce persistent anxiety towards interpersonal relationships and exaggerated levels of negative affect (Caspers et al, 2006). Insecure attachment is hypothesized to predict maladaptive emotional regulation and clinical theories of borderline personality disorder identify attachment insecurity as the basis of its characteristic disturbed interpersonal functioning (Choi-Kain et al, 2009).…”
Section: Attachment Theorymentioning
confidence: 99%
“…Thus, disorganization of the attachment system during infancy (Fonagy, Luyten, Batenian, Gergely, Strathearn, Target, & Allison, 2010) predisposes to separateness intolerance, as a core item of BPD pathology (Choi-Kain, Fitzmaurice, Zanarini, Laverdière, & Gunderson, 2009;Steele & Siever, 2010). b) Individual vulnerability and adverse life events may interact to lead to the disorder (Leichsenring et al, 2011), but the role of trauma in the BPD development remains unclear.…”
Section: Remarks On Bpd Psychopathologymentioning
confidence: 99%
“…Some evidence suggests that long-term treatments could be useful in avoiding premature ruptures in the therapeutic alliance with patients with attachment disturbances (Choi-Kain et al, 2009), early defective and conflicting experiences. Nevertheless these approaches are often unavailable due to insufficient resources and do not resemble treatment as usual (TAU), which is characterized in general by pharmacotherapy, rehabilitative interventions and unstructured psychological supports, although no research has examined it in detail (Paris, 2010).…”
Section: Treatment Problematic Issuesmentioning
confidence: 99%